2002
DOI: 10.1289/ehp.02110813
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of fumonisin B1, diethylnitrosamine, and catechol on the SNO esophageal cancer cell line.

Abstract: Mycotoxins that commonly contaminate staple food grains pose a health hazard to animals and humans. Fumonisin B1 (FB1), a mycotoxin produced by Fusarium verticillioides, causes equine leukoencephalomalacia and porcine pulmonary edema and has been implicated in the etiology of esophageal cancer (EC) in the Transkei, South Africa. Various studies have indicated that nitrosamines induce EC, and F. verticillioides enhancement of nitrosamine-induced EC in rats has been reported. Dietary catechol (CAT), a constituen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 17 publications
0
21
1
Order By: Relevance
“…One of the main reasons for the high incidence rates in these areas is believed to be the presence of the mycotoxin fumonisin B1 (FB1). It occurs in high concentrations in the above-mentioned geographic areas due to a soil-borne fungus named Fusarium verticillioides, which frequently contaminates maize and maize products [5,6]. Studies revealed that FB1 may act as a promoter or initiator of carcinogenesis in synergy with co-carcinogens such as the N-nitrosamines found in tobacco [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main reasons for the high incidence rates in these areas is believed to be the presence of the mycotoxin fumonisin B1 (FB1). It occurs in high concentrations in the above-mentioned geographic areas due to a soil-borne fungus named Fusarium verticillioides, which frequently contaminates maize and maize products [5,6]. Studies revealed that FB1 may act as a promoter or initiator of carcinogenesis in synergy with co-carcinogens such as the N-nitrosamines found in tobacco [6].…”
Section: Introductionmentioning
confidence: 99%
“…It occurs in high concentrations in the above-mentioned geographic areas due to a soil-borne fungus named Fusarium verticillioides, which frequently contaminates maize and maize products [5,6]. Studies revealed that FB1 may act as a promoter or initiator of carcinogenesis in synergy with co-carcinogens such as the N-nitrosamines found in tobacco [6]. One of the best-known characteristics of cancer cells is their rapid and uncontrolled division.…”
Section: Introductionmentioning
confidence: 99%
“…Most of all of the toxicities resulting from exposure to these compounds can be explained by their ability to alter sphingolipid metabolism [6] by inhibiting ceramide synthase [3]. Human consumption of fumonisin-contaminated corn has been linked to the esophageal cancer in different area of South Africa (Transkey) [7] and China (Linxian) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Catechol is not toxic to glioblastoma cells at concentrations below 0.2 mM [30]; however, it induces a 44% increase in esophageal cell death at 35 µM [4], suggesting that it exhibits differential cytotoxicity that is cell type-dependent.…”
Section: Discussionmentioning
confidence: 96%